Is Coronary Artery Ectasia a Progressive Disease? A Self-Controlled Retrospective Cohort Study - Liu, Ruifeng; Zhao, Huiqiang; Gao, Xiangyu; Liang, Siwen (Frontiers in Cardiovascular Medicine, 2021)
[Objective] It is essential to understand whether coronary artery ectasia (CAE) progresses over time because the patients might be under the risk of coronary rupture, and stent implant should be avoided if ectatic changes progress. [Methods] A consecutive series of 99 CAE patients who had undergone coronary angiography at least twice were enrolled and followed up for 1 to 16 years until they received a second angiogram. Subjects were divided into two groups (1–5 vs. 5–16 years of follow-up), then the basic clinical characteristics and coronary artery images were compared over time. [Results] (1) All CAE patients exhibited atherosclerosis, and a majority presented with acute myocardial infarction. Most baseline clinical characteristics were relatively stable. (2) Atherosclerosis (indicated by the distribution of stenosis in coronary vessels) and the Gensini scores progressed significantly. Ectasia extent showed minimal changes as indicated by blood vessel involvement, Markis type, coronary blood flow, ectasia diameter, and ectasia length. (3) Multilinear regression analysis revealed that the underlying factors related to stenosis evolution indicated by fold of Gensini score were: longer time interval, lower baseline Gensini score, and higher hypersensitive C-reactive protein concentration. (4) There was a relationship between the ectatic diameter and the extent of stenosis. [Conclusions] For CAE patients with atherosclerosis followed for 1 to 16 years, there was minimal CAE progression, while the atherosclerosis progressed and the ectasia extentwas related to degree of stenosis. The results indicate that prevention and treatment of atherosclerotic changes might have more clinical significance than addressing ectatic changes.